2024
DOI: 10.1128/msphere.00553-23
|View full text |Cite
|
Sign up to set email alerts
|

Resistance, mechanism, and fitness cost of specific bacteriophages for Pseudomonas aeruginosa

Luozhu Feng,
Huanchang Chen,
Changrui Qian
et al.

Abstract: The bacteriophage is an effective adjunct to existing antibiotic therapy; however, in the course of bacteriophage therapy, host bacteria will develop resistance to bacteriophages, thus affecting the efficacy. Therefore, it is important to describe how bacteria evade bacteriophage attack and the consequences of the biological changes that accompany the development of bacteriophage resistance before the bacteriophage is applied. The specific bacteriophage vB3530 of Pseudomonas aeruginosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The results also suggest that LPS-targeting phages can also be used to indirectly induce a fitness trade-off via drug efflux pump function. Recently, Feng et al (2024) also demonstrated that resistance variants against a LPS-targeting phage exhibit extensive chromosomal deletions, including 290 genes such as galU, hmgA, mexX , and mexY . This deletion revealed increased susceptibility to aminoglycosides and chlorhexidine, likely due to the loss of mexX expression ( Feng et al, 2024 ).…”
Section: Subsectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also suggest that LPS-targeting phages can also be used to indirectly induce a fitness trade-off via drug efflux pump function. Recently, Feng et al (2024) also demonstrated that resistance variants against a LPS-targeting phage exhibit extensive chromosomal deletions, including 290 genes such as galU, hmgA, mexX , and mexY . This deletion revealed increased susceptibility to aminoglycosides and chlorhexidine, likely due to the loss of mexX expression ( Feng et al, 2024 ).…”
Section: Subsectionsmentioning
confidence: 99%
“…Recently, Feng et al (2024) also demonstrated that resistance variants against a LPS-targeting phage exhibit extensive chromosomal deletions, including 290 genes such as galU, hmgA, mexX , and mexY . This deletion revealed increased susceptibility to aminoglycosides and chlorhexidine, likely due to the loss of mexX expression ( Feng et al, 2024 ). On the other hand, large chromosomal deletions containing mexX and mexY have also been reported to elicit resistance against ΦPIAS which is presumed to infect via the MexY as a receptor ( Koderi Valappil et al, 2021 ).…”
Section: Subsectionsmentioning
confidence: 99%